Old made new : a postmodern investigation into Mario Vargas Llosa's El Hablador and Thomas Pynchon's The crying of lot 49 - Salam, Upashana (BRAC University, 2010)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2009.